Development of a falls risk assessment and management tool for older adult mental health units - Tohotoa, J.; Wynaden, Dianne; Heslop, Karen (Science Med Central, 2016)
Fall prevention in Western Australian hospitals is monitored with a monthly generic falls assessment/management tool. Whilst this practice is suitable for bed ridden patients, it fails to capture the falls risk for older adult mental health patients who are predominantly ambulant and frequently confused. This paper describes the development of a specific mental health falls risk management tool (MHFRMT) for use in older adult mental health units. The development of this tool evolved from formative focus group research which successfully identified relevant predictors of risks for falls in this population. Corresponding management strategies were then developed for each criterion to the assessed levels of risk. Fall prevention management strategies included referral to physiotherapists for gait and balance testing, referral to occupational therapists for functional ability status and to podiatry for foot care. The new tool was initially piloted across three older adult mental health units in Western Australia with staff feedback resulting in some formatting revisions. The tool was then piloted at a fourth older adult mental unit with no further revisions required. The result was a new tool encompassing a weekly assessment rather monthly like the current generic falls form. Staff feedback was mainly about the format of the new tool rather than the content, suggesting that future studies need to focus on investigating the reliability and validity of the MHFRMT. Finally, although some staff were not happy with the increased work load associated with a weekly assessment, the weekly reporting highlighted two key issues in this patient group over three weeks: (1) fluctuating cognition and (2) mental state and behaviour changes. Additionally, the medication alert system identified the number of medications that increase falls risk and also indicated the risk alert level associated with each medication.